Konsep Pengelolaan Pendistribusian Pangan pada Pusat Distribusi di Provinsi Banten - Syaina Ulfah Azhara; Heru Winarno; Mohammad Bob Anthony; Firyaliza Dwi Putri (Pusat Riset dan Inovasi Nasional, 2025)
The rice supply chain process starts with farmers who harvest rice and sell it to Regional Owned Enterprises (BUMD) through Bank BJB and Bank Banten based on a price agreement. The rice is then processed in the Rice Milling Unit (RMU) to become ready-to-process rice, before being sent to the warehouse receipt as a guarantee of economic value. From the warehouse receipt, rice is sent to the distribution center which functions as a stock buffer and price determiner, then distributed to consumers. The distribution problem is less than optimal and rice is often sold outside the region, then back to regional distributors, causing an imbalance between food needs and availability. This research aims to illuminate supply chain management in distribution centers and the facilities used in the process. To reduce distribution costs, the transportation method uses the Vogel Approximation Method (VAM) and MODI is used to find the minimum distribution costs. The research results show that the minimum distribution costs in 2017 were IDR 1,024,557,000,000, in 2018 IDR 1,024,107,000,000, 2019 IDR 1,020,428,000,000, 2020 IDR 1,089,830,000,000, and 2021 amounting to IDR 1,111,159,000,000.